Safety Assessment of One Day Treatment of Liquorice Extract in Female Sprague Dawley Rats - Cheang Weng Yee; Loh Yi Qing; Endarutenne Gedara Mohamed Rizwan Fathima Naathiya; Anastasia Annabella Goh Hui Xin; Chee Jing Tung; Chen Hong-Ze; Coen Tan Mun Shun; Darren Voo; Jameel Muhammad Aathiq; Tay Yu Dung; Wong Xianglin; Yuzhu Liu; et al. (Malaysian Journal of Science (MJS), 2025)
This study aimed to provide preliminary data on the safe use of liquorice extracts for herbal product consumers. Female Sprague Dawley rats received a single-day treatment with liquorice extract (50–2000 mg/kg) or distilled water (control). Liver and kidney functions were evaluated through blood biochemical analysis, gross, and histological evaluation. This animal study adhered to the OECD Test Guideline 423. Fifteen female SD rats, aged 16 weeks, were randomly assigned to five groups (n = 3). The control group received distilled water, while treatment groups T1, T2, T3, and T4 were administered liquorice extract at doses of 2000, 200, 100, and 50 mg/kg via oral gavage. Body and organ weights (liver, kidney, heart) were measured. Blood samples were collected to assess serum biochemical markers, including alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT), creatinine, and urea levels. Data were analysed using Dunnett’s tests, with p < 0.05 denoting statistical significance. No significant changes in body or organ weights occurred across groups. Liquorice extract had no effect on ALT or GGT. Serum creatinine decreased (p < 0.05) at 200 mg/kg, and serum urea decreased at 50 mg/kg compared with controls. A single-day liquorice extract treatment (50–2000 mg/kg) was safe and caused no hepatic or renal toxicity in female SD rats.